Patient initiation and maintenance of GLP-1 RAs for treatment of obesity. Issue 10 (3rd October 2021) - Patel, Dhiren; Smith, April
ABSTRACT: Introduction: Healthcare providers (HCPs) see many patients with obesity-related complications and are therefore well placed to help treat obesity itself. However, limited collated information exists to help HCPs with the practical use of anti-obesity medications (AOMs). We focus on the initiation and maintenance of a glucagon-like peptide-1 receptor agonist (GLP-1 RA) for weight management, liraglutide 3.0 mg. Literature search was conducted between 25–28 November 2019 on PubMed and ClinicalTrials.gov. Areas covered: Clinical trial and real-world data describing weight-loss efficacy, cardiometabolic risk factors, incidence of adverse events (AEs), and persistence are presented to assist HCPs with patient discussions. Practical considerations to overcome barriers to optimal use are provided, equipping HCPs with the information required to aid with adherence to and persistence with AOMs. The use of other GLP-1- RA therapies in obesity is discussed in light of the recent US Food and Drug Administration approval of semaglutide 2.4 mg for weight management. Expert opinion: Liraglutide 3.0 mg provides benefits regarding weight loss and improvements in cardiometabolic risk factors. Promising areas of future research in the field of obesity include dual receptor agonists and the combination of glucagon-like peptide-1 receptor agonists with other molecules.